The Synergistic Effects of the Particle Elongation Index and Flat Index on Aggregate Strength and Dilatancy: A Discrete Element Method Study - Yiming Liu; Zhangshuaihang Cao; Haijun Mao (Applied Sciences)
To address the limitations in conventional granular morphology characterization where excessive emphasis has been placed on elongation index (EI) while neglecting flatness index (FI) and their coupled interactions, this study establishes an EI/FI co-regulated dual-parameter morphological characterization framework. Through integrated triaxial compression experiments and discrete element simulations, we systematically investigate multi-scale mechanical responses spanning macroscopic stress–strain behavior to microscopic force-chain evolution. The results show that (1) the regulation of pore structure by morphological parameters presents non-linear characteristics, and (2) the evolution of peak shear strength is predominantly governed by morphological anisotropy. (3) The parabolic relationship between the maximum dilatancy angle and the morphological parameters is shown. (4) The micro mechanical analysis reveals that EI/FI parameters have limited influence on the statistical distribution characteristics of the contact force chain, but have a significant regulatory effect on the anisotropic evolution of the force-chain network.